Economic Development-Based on Local Tourism in Yogyakarta - Asworo, Listiana (Government Studies of Muhammadiyah Malang University/AIPPTM, 2018)
Tourism sector has long been referred to as economic sector. It is believed that tourism is one of the factors causing multiplier effect that result in welfare on one side and community empowerement on another side. In order to realize the multiplier, effect all stakeholders should work in a synergy to develop tourism-based local economics. The article described how bottom-up approach, empowerement and local wisdom had given positive contribution towards tourism sector in Gua Pindul and at the same time improved the local economics.